Factibilidad económica para la comercialización de presas seleccionadas selladas al vacío en pollos criollos “Gallusgallusdomesticus” - Párraga Delgado, Sindy del Rocío (2013)
The objective of this research is to determine the economic feasibility for commercialization of selected dams vacuum sealed Creole chickens (Gallus gallus domesticus), to contribute to the socio-economic development of the parish Sock. The feasibility study understood the market, the technical study and financial study. The market research survey was carried out by 382 people chosen at random, who were asked about consumption of chicken and its quality. The technical study it conducted a pilot test in which we observed the processes of slaughter of chickens to reach the final product. The study analyzed financial indicators such as cash flow; profit and loss states the IRR, NPV and TAD. The market study is feasible reflection marketing chicken selected dams. Turn to the technical study could know the process and avoid possible errors when vacuum sealing. Since economically and financially reflected the following results: the Net Present Value (NPV 44 722.45), the Internal Rate of Return (IRR 30%) and discount rate (TAD 19.76%). According to the results obtained it was concluded that it is feasible commercialization of chicken’s creole vacuum sealed Calceta City.